The principal : three keys to maximizing impact / Michael Fullan. - Fullan, Michael (San Francisco : Jossey-Bass, 2014)
'The author of Six Secrets of Change describes how and why the principal's role must change to maximize student achievementPrincipals are often called the second most crucial in-school influencers (after teachers) of student learning. But what should the principal do in order to maximize student achievement? One of the best-known leadership authors in education, Fullan explains why the answer lies neither in micro-managing instruction nor in autonomous entrepreneurialism. He shows systematically how the principal's role should change, demonstrating how it can be done in short order, at scale. Reveals the three key roles that administrators must play in today's schools Explains how to choose the right versus wrong drivers of school success Filled with'action items' to help implement Fullan's program effectively Includes strategies that have been successfully field-tested in schools across the United States and Canada '--
Includes bibliographical references (p. 161-167) and index.
Keywords: School principals; Educational leadership; Educational change; Educational innovations; School management and organization